Adverse Effects of Lead Acetate on Light Weight Protein of Bactrocera dorsalis - Rizwanul Haq; M. Farhanullah Khan; Ehteshamul Haq (Journal of Basic & Applied Sciences, 2021)
ALarge number of insects are influenced easily by a number of pollutants; such as, the influence of lead (as lead acetate) on Bactrocera dorsalis. Lead is considered to be an important toxic waste which could contaminate the environment, such as soil, air and water. Therefore, insects could be influenced by the lead. Bactrocera dorsalis, was studied at 48 hours post treatment, under the effects of lead acetate, in different concentrations. Lead is found to exert a definite specific physiological and morphological effect on these flies. It was observed that under the effect of lead abnormalities and deformities were developed in the larvae of flies. Thus these flies could present a useful module for the quick transmission of the environmental hazards due to lead contamination, which exerts a specific physiological and morphological effect on these flies. The purpose of the present work was to determine the effects of lead on proteins as a major indicator of physiological features along with morphological features of larvae of Bactrocera dorsalis flies.